2020
DOI: 10.1002/anie.201912719
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Conversion of CO2 to Syngas with Controllable CO/H2 Ratios over Co and Ni Single‐Atom Catalysts

Abstract: The electrochemical CO2 reduction reaction (CO2RR) to yield synthesis gas (syngas, CO and H2) has been considered as a promising method to realize the net reduction in CO2 emission. However, it is challenging to balance the CO2RR activity and the CO/H2 ratio. To address this issue, nitrogen‐doped carbon supported single‐atom catalysts are designed as electrocatalysts to produce syngas from CO2RR. While Co and Ni single‐atom catalysts are selective in producing H2 and CO, respectively, electrocatalysts containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(148 citation statements)
references
References 30 publications
1
146
1
Order By: Relevance
“…Further stabilization of *HOCO is expected due to the formation of hydrogen bonds (0–0.15 eV/hydrogen bond) with water molecules, indicating a thermodynamically favored CO 2 RR at electrochemical conditions compared to gas‐phase DFT calculated energetics. [ 36–39 ] Additionally, the desorption of weakly bound *CO (BE = −0.02 eV) is predicted to be significantly facilitated on PdN 4 compared to Pd/PdH. Therefore, in agreement with the experimental observations, DFT predicts an enhanced CO 2 RR on PdN 4 single‐atom site compared to Pd/PdH and Pd nanoparticles supported on graphene.…”
Section: Resultssupporting
confidence: 70%
“…Further stabilization of *HOCO is expected due to the formation of hydrogen bonds (0–0.15 eV/hydrogen bond) with water molecules, indicating a thermodynamically favored CO 2 RR at electrochemical conditions compared to gas‐phase DFT calculated energetics. [ 36–39 ] Additionally, the desorption of weakly bound *CO (BE = −0.02 eV) is predicted to be significantly facilitated on PdN 4 compared to Pd/PdH. Therefore, in agreement with the experimental observations, DFT predicts an enhanced CO 2 RR on PdN 4 single‐atom site compared to Pd/PdH and Pd nanoparticles supported on graphene.…”
Section: Resultssupporting
confidence: 70%
“…DFT results indicate that the formation of *COOH is the rate‐limiting step, and the Zn‐N 4 single atoms work as the active site for ECR and decrease the energy barrier [77] . Chen and co‐workers developed a nitrogen‐doped carbon supported Ni and Co single‐atom catalyst (CoNi‐NC) as an ECR catalyst [78] . The as‐prepared CoNi‐NC shows high catalytic activity (total current density >74 mA cm −2 at a potential of −1.0 V vs. RHE) and tunable CO/H 2 ratios (0.23–3.26).…”
Section: Nanostructured Materials As Catalysts For Cdrrmentioning
confidence: 99%
“…[26][27][28] Recently, Co single atom catalysts have been demonstrated high activity towards photocatalysis and electrochemical syngas production. [29][30][31] Through reviewing the published works, we found that the research on amorphous Co-based compounds remains deficient. Besides, the simultaneous high-efficiency evolution of syngas is still challenging.…”
mentioning
confidence: 99%